Paradigma Filsafat Kosntruktivisme dalam Pembelajaran Fisika - Hayang Sugeng Santosa; Naharul Fitri (IKIP Budi Utomo Malang, 2022)
According to its essence, physics consists of three meanings, namely physics as: 1) product, 2 attitude, and 3) process. Physics learning that is carried out adapts to its nature in line with the philosophical thoughts of constructivism put forward by Jean Piaget. Physics learning can be done by paying attention to the three principles of constructivism, namely knowledge: 1) formed by students; 2) is a social outcome; and 3) can always change. This research is qualitative with the library research method. The research data was obtained from a literature review of reference books and research journals. Based on the research results, learning physics in the view of the constructivism paradigm can be studied from several aspects, namely the learning process, the role of students, the learning process, the role of the teacher, learning strategies, and learning evaluation.